Accumulation of rectum dose‐volume metrics for prostate external beam radiotherapy combined with brachytherapy: Evaluating deformably registered dose distribution addition using parameter‐based addition. Issue 4 (9th February 2017) - Moulton, Calyn R; House, Michael J; Lye, Victoria; Tang, Colin I; Krawiec, Michele; Joseph, David J; Denham, James W; Ebert, Martin A
Abstract: Introduction: To investigate the accuracy of deriving dose‐volume histogram (DVH) parameters from deformably registered data by comparing values with the simple addition of DVHs from each phase of a combined external beam radiotherapy (EBRT)/high‐dose‐rate (HDR‐BT) brachytherapy prostate treatment. Methods: Eighty‐two patients received EBRT in 23 fractions of 2 Gy and HDR‐BT TG43 in three fractions of 6.5 Gy. The HDR‐BT CT was deformably registered to the EBRT CT. The rectum D0.1cc, D1cc, D2cc and D10cc were calculated in two ways. (i) Parameter‐adding: the EBRT DVH parameters (or the EBRT prescription dose) were added to the unregistered HDR‐BT DVH parameters. (ii) Distribution‐adding: the parameters were extracted after the EBRT doses were 3D‐summed with the registered HDR‐BT doses. Resulting differences between the parameters were investigated. Results: The D0.1cc, D1cc and D2cc from parameter‐adding were 21.3% ( P  < 0.001), 6.3% ( P  < 0.001) and 3.5% ( P  < 0.001) smaller than those from distribution‐adding. The D10cc was 2.2% ( P  = 0.015) larger for distribution‐adding. Conclusion: Distribution‐adding was confounded by unsystematic inter/intra‐observer rectum‐contouring errors and registration accuracy near the anterior rectal wall. Consequently, clinical use of distribution‐adding to assess rectal doses requires careful contour and registration evaluation.